Computer-mediated communication and the reduction of prejudice: A controlled longitudinal field experiment among Jews and Arabs in Israel - Walther, Joseph B.; Hoter, Elaine; Ganayem, Asmaa; Shonfeld, Miri (Computers in human behavior, 2015)
•Prejudice among Israeli Jews and Arabs’ declined in yearlong virtual teams.•A longitudinal design and post-test control groups enhance causal conclusions.•The study integrates CMC theory with the intergroup contact hypothesis.•Interpersonal factors correlate with better attitudes toward outgroups as a whole. The promise of computer-mediated communication (CMC) to reduce intergroup prejudice has generated mixed results. Theories of CMC yield alternative and mutually exclusive explanations about mechanisms by which CMC fosters relationships online with potential to ameliorate prejudice. This research tests contact-hypothesis predictions and two CMC theories on multicultural, virtual groups who communicated during a yearlong online course focusing on educational technology. Groups included students from the three major Israeli education sectors—religious Jews, secular Jews, and Muslims—who completed pretest and posttest prejudice measures. Two sets of control subjects who did not participate in virtual groups provided comparative data. An interaction of the virtual groups experience×religious/cultural membership affected prejudice toward different religious/cultural target groups, by reducing prejudice toward the respective outgroups for whom the greatest initial enmity existed. Comparisons of virtual group participants to control subjects further support the influence of the online experience. Correlations between prejudice with group identification and with interpersonal measures differentiate which theoretical processes pertained.